Building Community Participation through Participatory Oversight in the 2024 Simultaneous Elections - Mahyudin, Mahyudin; Samburoto, Yuyun; Alfinta, Muhammat Alim; Candra, Candra; Sampe, Silas Adian (Edumedia Solution, 2023)
Democratic elections require public involvement in all stages of the electoral process, including election monitoring itself. This community service project is carried out with the aim of helping novice voters understand the importance of participatory supervisors in the simultaneous elections of South Buton Regency in 2024. The answer to the occurrence of election violations is the existence of participatory supervisors, which will be able to assist and facilitate the task of supervisory institutions in supervising sustainable democratic participants, this is done for the sake of creating honest, fair, clean and integrity elections. Then Bawaslu must provide thorough training and direction to participatory supervisors so that they know and fully understand their duties and obligations in overseeing the democratic party. After this service activity is carried out, the output objectives to be achieved are patterns of knowledge and awareness of the relevance of participatory supervision in the 2024 simultaneous elections in the South Buton region. This activity was carried out through socialization, therapy, and questions and answers. The result of this community service activity is the existence of participatory supervisors in the elections in South Buton district, which will provide awareness for political actors, election organizers, and stakeholders to take care of themselves, maintain the spirit of their parties to stay on the rails according to their respective portions, so as to produce post-conflict elections that are honest, fair, and have integrity both in terms of process and results.